The look as a medium: a conceptual framework and an exercise for teaching visual studies. Issue 1 (3rd April 2019) - Lehmuskallio, Asko
Abstract: The paper considers the particular value of focusing on the look as a medium when studying visual cultures. This focus is helpful for coming to terms with distinct understandings of the visual. To address the look as a medium, four analytical dimensions are introduced for distinguishing among separate but closely interrelated visual phenomena: the look becomes understandable via its mediations, some media are explicitly created to be looked at, the look itself acts as a medium of images and looking is a skilled practice that must be learned. In light of the approach outlined, an exercise is presented for teaching the look as a medium at university level: this exercise in 'looking into each other's eyes' is applied with the aim of sparking interest in the topic and stimulating debate on its various dimensions. Thus, it is intended to be generative, an exercise to think with.